Hubungan Tingkat Kecanduan Judi Online Dengan Perilaku Seks Bebas Pada Remaja Di Kelurahan Tugu Cimanggis Depok Tahun 2023 - Rizka Daniah; Arif Hidayatullah; Susaldi Susaldi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
In the era of globalization, the development of increasingly sophisticated information technology not only makes it easier to carry out online activities but can also be exploited, as in the case of online gambling. The decline of the country's economy and the morale of its youth are two direct effects of Indonesia's growing online gambling market. Research Objective: To determine the relationship between the level of online gambling addiction and casual sexual behavior among teenagers in Tugu Cimanggis Village, Depok in 2023. The research uses a quantitative type with a correlational descriptive design. The research population was 133 respondents in Tugu Cimanggis Village, Depok. The sampling technique used in the research was non-probability sampling with purposive sampling. Data collection uses a questionnaire via Google Form. Research Results: The research results show that there is a significant relationship between the level of online gambling addiction and free sexual behavior among teenagers in Tugu Cimanggis Village, Depok in 2023 (p value 0.002). There is a relationship between the level of online gambling addiction and promiscuous sexual behavior among teenagers in Tugu Cimanggis Village, Depok in 2023.